Refolding of recombinant Pneumocystis carinii dihydrofolate reductase and characterization of the enzyme. - Delves, C; Ballantine, S; Tansik, R; Baccanari, D; Stammers, D (1993)
The isolation of dihydrofolate reductase (DHFR) cDNA sequences from the messenger RNA of Pneumocystis carinii using the polymerase chain reaction is described. The 206-amino acid P. carinii DHFR was expressed to high levels in Escherichia coli inclusion bodies using the T7 promoter expression system. Solubilization of the inclusion bodies in 4 M guanidine hydrochloride and refolding of the recombinant protein in the presence of 0.5% polyethylene glycol 1450 yielded correctly folded DHFR which was purified to homogeneity by methotrexate-Sepharose affinity chromatography. The refolded enzyme was readily crystallized as a ternary complex with NADPH and various inhibitors. The enzyme exhibited a sharp pH optimum with maximum activity at pH 7.0 (turnover number = 6500 min-1). Km values for dihydrofolate (DHF) and NADPH were 2.3 and 3.0 microM, respectively, in 0.1 m imidazole buffer, pH 7. Folate did not act as a substrate. Comparison of the kinetic properties of the refolded enzyme with soluble P. carinii DHFR expressed at low levels in the T7 expression system showed similar pH-activity profiles, Km values for DHF and NADPH, and IC50 values for several known antifolates which were tested as inhibitors of the enzyme.